Tear Film Osmolarity Measurement in Japanese Dry Eye Patients Using a Handheld Osmolarity System - Jun Shimazaki; Miki Sakata; Seika Den; Miki Iwasaki; Ikuko Toda (Diagnostics, 2020)
We studied the efficacy and safety of a handheld osmolarity measurement system (I-PEN) in Japanese patients with dry eye disease (DED) and non-DED subjects. In this prospective, multicenter study, tear osmolarity was examined using the I-PEN in a total of 122 eyes divided into DED (n = 71) and non-DED (n = 51) groups. Subjective symptoms were assessed using the Dry Eye-Related Quality-of-Life Score (DEQS) questionnaire. Ocular surface condition was evaluated in terms of fluorescein tear breakup time (FBUT) and tear breakup pattern (TBUP), and by fluorescein staining and Schirmer’s test. The I-PEN measurements were performed safely in the majority of cases. There was no statistically significant difference in mean tear film osmolarity between the DED and non-DED groups (294.76 ± 16.39 vs. 297.76 ± 16.72 mOsms/L, respectively, p = 0.32). No significant correlations were observed between osmolarity values and DEQS score, FBUT, or the Schirmer score. Osmolarity did not differ among TBUP subgroups. This prospective clinical study found no correlations between the tear film osmolarity values obtained with the I-PEN system and any subjective or objective parameters of DED. Further studies are required to determine the utility of the I-PEN system in other settings.